Nurses’ Moral Distress in the Emergency Department - Efri Widianti; Rani Arinda; Ayu Prawesti (Journal of Nursing Care, 2019)
The failure of nurses in taking action related to their moral beliefs makes nurses' moral comfort not achieved and affects their dissatisfaction in their work, perhaps it also can result in nurses'  distress. The purpose of this study was to identify moral distress in the Emergency Department (ED) nurses. The study design used quantitative descriptive with a cross-sectional approach. the instrument used was the moral distress scale-revised (MDS-R) which measures the frequency and intensity of moral distress. The sampling technique used is total sampling. the sample population in this study was ED nurses in one type a hospital in Bandung, with a sample of 51 people. The results showed that the average of the total moral distress in emergency nurses was 50.72 (sd 43.846) and showed that moral distress in ed nurses tended to be low. the duration of nurse work experience is an individual factor that significantly influences moral distress in ed nurses. There is no significant difference in the mean moral distress score with the nurse's intention to quit his job. Qualitative research is needed to determine the causes of other moral distress and moral distress explanations can be given to nurses and students to increase the sensitivity and moral competence of Indonesian nurses.